DESIGN INFORMATION SYSTEM ONLINE REGISTRATION VACCINE COVID-19 AT RSAU DR. M. SALAMUN - Yuda Syahidin; Elza Dewiana Mahpud; Debora Serina Br Tarigan; Meira Hidayati (STMIK Royal, 2022)
Abstract: The entry of Covid-19 into Indonesia has caused many people to be affected, for example is delay in many activities and the increasing spread of the virus that affects public panic. One way to prevent the spread of the virus is the vaccination. Vaccination is the process of administering the vaccine that is useful for providing immunity to a certain disease in a person’s body. With vaccination, it will strengthen the community’s immune system. To make it easier for the public, vaccination registration can be done online now. Filling in the data can be done from home, so that it does not cause long queues that allow the risk of new clusters. The public will get proof of registration, which must be screenshots in the form of a barcode accompanied by a queue number and any prerequisites that must be brought when they come to. On the other hand, it will also be easier for health workers to confirm the suitability of the registered data with the person who came for the vaccine. The research used is descriptive research with observational and interview methods. The design of this system using the web with PHP programming language and MySQL database. Keywords: information system; registration; vaccination Abstrak: Masuknya Covid-19 ke Indonesia menyebabkan banyaknya masyarakat yang terkena dampaknya, contohnya yaitu terhambatnya banyak aktivitas dan meningkatnya penyebaran virus mempengaruhi kepanikan masyarakat. Salah satu cara untuk mencegah penyebaran virus ini adalah dengan melakukan vaksinasi. Vaksinasi adalah proses pemberian vaksin yang berguna untuk memberikan kekebalan terhadap suatu penyakit tertentu ke dalam tubuh seseorang. Dengan adanya vaksinasi, maka akan memperkuat sistem imun masyarakat. Untuk mempermudah masyarakat maka saat ini pendaftaran vaksinasi dapat dilakukan secara online. Pengisian data dapat dilakukan dari rumah, agar tidak menyebabkan antrian panjang yang memungkinkan adanya resiko cluster baru. Masyarakat akan mendapatkan bukti pendaftaran yang harus di screenshoot berupa barcode disertai nomor antrian dan persyaratan apa saja yang wajib dibawa saat akan datang melakukan vaksinasi. Di sisi lain, petugas kesehatan pun akan lebih mudah dalam mengonfirmasi kesesuaian data yang terdaftar dengan orang yang datang melakukan vaksin. Penelitian yang digunakan adalah penelitian deskriprif dengan metode observasional dan wawancara. Perancangan sistem ini dilakukan menggunakan web dengan bahasa pemrograman PHP dan database MySQL. Kata Kunci: registrasi; sistem informasi; vaksin